The craft of editing : - Alley, Michael (Springer, 2000)
The Craft of Editing is about the craft of editing scientific and technical writing. It is designed to help you - and all those who deal with scientific and technical writing in businesses, engineering firms, government labs, or universities - become more effective and more efficient at editing the proposals, theses, journal articles, and reports that cross your desk and that you must approve, grade, or review. Unlike other texts that try to present all possible editing experiences, this guide focuses on the kind of editing that you as a manager, scientist, or engineer perform with your pencil (or computer) and someone else's work